Integration of catalytic fast pyrolysis and hydroprocessing: a pathway to refinery intermediates and "drop-in" fuels from biomass. Issue 22 (8th September 2016) - Mante, Ofei D.; Dayton, David C.; Gabrielsen, Jostein; Ammitzboll, Nadia L.; Barbee, David; Verdier, Sylvain; Wang, Kaige
Abstract : Biocrude obtained from catalytic fast pyrolysis could be hydrotreated in a single-stage without preprocessing and stabilization steps. Abstract : Single-stage hydrotreating (HDT) of loblolly pine biocrude produced from catalytic pyrolysis was conducted to gain insight to HDT performance in terms of product yields, liquid product quality, and hydrogen consumption. Tests were performed with a sulfided HDT catalyst at three different conditions. The longest continuous time onstream operation (365 h) was achieved at an average bed temperature of 290 °C, 138 bar pressure, H2 /oil ratio of 3300 Nl l −1, and a liquid hourly space velocity (LHSV) of 0.25 h −1 . The average carbon yield of the HDT liquids were 77%, 83%, and 89% for experiments 1, 2, and 3, respectively. Also, the biocrude carbon that ended up in the gas phase varied between 4.3% and 8.9%. The carbon in the aqueous phase fraction was negligible—less than 0.5% of the biocrude carbon. The average hydrogen consumed ranged from 0.04 g to 0.07 g per 1 g of dry biocrude. The highest carbon content measured for the HDT liquid products from all three experiments was 87.13 wt% and the lowest was 79.03 wt%. GC-MS analysis suggests that the HDT product with oxygen content less than 5 wt% contained mainly naphthenic hydrocarbons. On the other hand, HDT products with oxygen content greater than 5 wt% contained a higher concentration of simple phenols and aromatic hydrocarbons (mono- and poly-). Catalyst deactivation was evident in the quality of the HDT liquid collected over time; the density and viscosity increased, the H/C ratio and carbon contents decreased; also, the gasoline fraction decreased while the gas oil fraction increased. The results from this work suggest that HDT of biocrude produced by catalytic biomass pyrolysis can be successfully upgraded into hydrocarbon liquid fuels without a stabilization step.